PENGARUH UKURAN PERUSAHAAN, INTENSITAS ASET TETAP DAN LEVERAGE TERHADAP REVALUASI ASET TETAP - Dewi, Anisa Aprilia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the effect of firm size, intensity fix asset and leverage to fix asset revaluation. In this research used explanation method. The variables studied are the independent variables is firm size, intensity fix asset and leverage while the dependent variable is the fix asset revaluation. Research population is state-owned enterprises (BUMN) company listed in Indonesia Stock Exchange (IDX), while sampling technique used is purposive sampling. However, rocessing techniques and data analysis used used are accounting analysis, descriptive statistical analysis and logistic regression analaysis, analysis using SPSS version 20.0. Based on the partial test of hypothesis firm size have a positive and significant effect on fix asset revaluation, but fix asset intensity and leverage no significant effect on fix asset revaluation. And simultaneously firm size, fix asset intensity and leverage have a positive and significant impact on fix asset revaluation.